The Effect of Informational Justice on Employees' Knowledge-Hidden Behavior With Organizational Identification as A Mediate at The Yogyakarta Main Post Office - Arimbi Intan Shalistasani; Ignatius Soni Kurniawan; Tri Ratna Purnamarini (Dinasti International Journal of Education Management and Social Science, 2025)
With organizational identity serving as a mediator, this study seeks to investigate the impact of information justice on knowledge hiding behavior. Using a census approach (saturated sample), the study population consisted of all workers of the Yogyakarta Main Post Office. Partial Least Square-Structural Equation Modeling (PLS-SEM) was used to examine data obtained from a 1–5 Likert scale questionnaire. Before evaluating the hypothesis, validity and reliability were carried out. To assess the suggested model, we used model fit, R-square, effect size (f²), and bootstrapping. The findings reveal that information justice exerts a significant positive effect on organizational identification and a significant negative effect on knowledge hiding behavior. Moreover, organizational identification demonstrates a significant negative effect on knowledge hiding behavior and effectively mediates the association between information justice and knowledge hiding behavior. The results show that when information justice is implemented, it decreases the inclination to participate in knowledge-hiding behavior both directly and indirectly, and it boosts organizational identity among employees. This demonstrates the importance of transparent, consistent, and honest communication practices in building a collaborative organizational climate and minimizing barriers to knowledge sharing. Consequently, organizations are encouraged to build a culture of openness to minimize knowledge hoarding.